Enjeux de professionnalisation et rapport à la formation des artistes équestres : approche d’un objet « complexe » soutenue par deux niveaux d’analyse - Thérèse Perez-Roux (Éducation et Socialisation)
Equestrian artists (EA), with their multiple characteristics, are poorly identified in the world of performing arts. The issue of professionalisation of the sector is not perceived in the same way by the actors concerned. The contribution focuses on the relationship of AEs to training and is based on a plural data collection: semi-directive interviews (n=31), and interviews carried out on the basis of traces of the activity in a prototypical training course. The latter, designed by a team of researchers in the context of technological research, was experienced in total immersion for a week (researchers and AEs). The inter-level approach makes it possible to understand the modes of learning favoured in the course of the AEs; moreover, it opens up the experience lived by the latter, engaged, with the researchers, in a training intended to test the proposals and to adjust the professionalization project. The results open up a reflection on what this research produces in terms of knowledge, and on what it engages/transforms at the collective and individual levels.